How Not to Waste a Garbage Crisis: Food Consumption, Solid Waste Management and Civic Activism in Bangalore/Bengaluru, India - Christine Lutringer; Shalini Randeria (Revue Internationale de Politique de Développement)
The editorial introduction by Christine Lutringer and Shalini Randeria delineates the overarching themes that are the foci of this special e-issue, namely the policy shifts and changes in practices of solid waste management in Bangalore following the 2012 ‘garbage crisis’. It suggests that civic mobilisation among the middle classes (and especially legal activism) have played a crucial role in the demand for, and partial implementation of, an efficient and sustainable solid waste management system. Crises and subsequent reforms thus constitute fruitful vantage points from which to explore larger processes of policy change. The contributions to this issue offer insights into the interplay between changing food consumption patterns, social practices of sustainable consumption, new forms of civic activism and emerging policy responses. On the one hand, they examine how middle-class engagement, through legal activism and neighbourhood mobilisation, has shaped public perceptions as well as public policies. On the other, the contributions combine insights into some important aspects of domestic and restaurant food production and consumption with an analysis of their implications for waste generation and disposal. Designing sustainable policies to address the environmental impact of changing food consumption patterns thus requires careful analysis of not only consumption practices at the level of the household but also of practices related to waste generation, prevention, segregation and disposal.